Biochemical Changes in Lowlanders on Descent to Plains after Prolonged Stay at High Altitude-A Cross-sectional Study - Singh, Som Nath; Shyam, Radhey; Vats, Praveen; Singh, Vijay Kumar; Das, Savita; Singh, Shashi Bala (Defence Science Journal, 2004)
The biochemical changes taking place in human subjects following de-induction to plains from high altitude (5700-6100 m) after a prolonged slay of 9-13 months were investigated in 120 soldieri in four groups of 30 each on day 5, 30, 60 and 90 after their descent. One group of soldiers, who were never posted at high altitude served as control. Haemoglobin levels, which were initiall,v hiueh after 5 dnvs of de-induction droooed lo sienificantlv lower levels in the erouo . L ., " . studied on day 60 after de-induction. No clinically abnormal changes were noted in activities of serum enzymes, ie, aspartate aminotransferase, alanine aminotransferase and y-glutamyl transpeptidase. Alanine aminotransferase activity was found significantly elevated in 5-day group (53.1 i0.24 IUII). Cholesterol and triglyceride levels were higher in 30-day group in comparison to groups studied on day 5,60 and 90 after de-induction from high altitude. Activity of glutathione S-transferase was more in groups studied on day 30 and 60 and may he in response to increased demand for detoxification of certain metabolites. Endogenous creatinine clearance was impaired with concomitant increase in serum creatinine levels. The creatinine clearance returned to normal only in group studied on day 90 after de-induction. Testosterone and estradiol levels were within normal physiological limits. However, there was increase in testosterone levels following ds- ~nductionR. esults of this cross-sectional study indicate that it takes 1-3 months after de-induction from high altitude for biochemical parameters to reach normal levels.